2014
DOI: 10.1074/jbc.m113.529958
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Regulator Mis18β Interacts with and Specifies the Centromeric Assembly of Molecular Chaperone Holliday Junction Recognition Protein (HJURP)

Abstract: Background: HJURP is a molecular chaperone essential for the deposition of the centromere marker CENP-A. Results: Mis18␤ binds with and specifies the centromere localization of HJURP. Conclusion: Mis18␤ governs centromere assembly via the Mis18␤-HJURP-CENP-A axis. Significance: Our finding reveals a novel mechanism underlying CENP-A incorporation into the centromere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 49 publications
(40 reference statements)
7
102
2
Order By: Relevance
“…HJURP is known to function in prenucleosomal CENP-A stabilization and in centromere deposition, by a mechanism that requires its dimerization (Zasadzińska et al, 2013), its binding to Mis18b (also known as OIP5) (Wang et al, 2014) and its DNA-binding activities (Müller et al, 2014). HJURP specifically recognizes CENP-A by interacting with the centromere-targeting domain (CATD; Black et al, 2007) of CENP-A to protect it from proteolysis (Foltz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HJURP is known to function in prenucleosomal CENP-A stabilization and in centromere deposition, by a mechanism that requires its dimerization (Zasadzińska et al, 2013), its binding to Mis18b (also known as OIP5) (Wang et al, 2014) and its DNA-binding activities (Müller et al, 2014). HJURP specifically recognizes CENP-A by interacting with the centromere-targeting domain (CATD; Black et al, 2007) of CENP-A to protect it from proteolysis (Foltz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Existing CENP-A nucleosomes directly recruit CENP-C, which in turn recruits the Mis18 complex during mitotic exit (6,7). Mis18 binding recruits HJURP and directs nascent CENP-A nucleosome assembly at an adjacent site (8). Despite the essential presence of the CENP-A nucleosome for centromere formation and maintenance, the centromere-specific nucleosomes are present within a context of chromatin containing post-translational modifications (PTMs) of histones that are thought to be important for centromere function, as outlined below.…”
mentioning
confidence: 99%
“…In fission yeast it was revealed that Scm3 could directly binding to Mis18 in vitro 78 . Our lab, along with others 60 , have established that the Mis18 complex does indeed have a direct interaction with HJURP in vitro and in vivo. These findings will be explained more in the second chapter of this work.…”
Section: Centromere Priming Components: Mis18mentioning
confidence: 99%
“…In this system Scm3 also binds to AT-rich DNA (which is enriched at budding yeast point centromeres) which could make this another avenue for Scm3 recruitment to centromeres 82 . Our lab (in specific the research in this paper) has found Mis18 and Scm3 interact in fission yeast and this interaction is conserved to humans where HJURP directly binds to the Mis18α-β complex 60 . We will show in this thesis that the physical interaction between Mis18 and HJURP/Scm3 is absolutely required for proper HJURP centromere recruitment and CENP-A deposition.…”
Section: Centromere Priming Components: Hjurpmentioning
confidence: 99%
See 1 more Smart Citation